Use of hate speech in Arabic language newspapers - Eissa, Sarah (AUC Knowledge Fountain, 2017)
This research aims to examine hate speech in the Egyptian Arabic language newspapers, through examining the front page of the three dailies, the state-owned Al-Ahram newspaper, the privately-owned newspaper Al-Masry Al-Youm and the partisan newspaper Al-Wafd. The study’s time span starts from June 30, 2012 to June 30, 2015. The analysis for the study is based on the framing and agenda-setting theories in order to find how hate speech is framed and whether the speech is affected by a governmental agenda. The research uses the quantitative method of content analysis to examine the total of 111 front pages. The research found that hate speech was used more by the privately-owned Al-Masry Al-Youm newspaper followed by Al-Wafd party newspaper, and finally by the state-owned Al-Ahram newspaper. The major sources of hate speech were journalists who used hate speech in their own words in their writing and reporting, the major hate speech victims were Islamists followed by others and the major type of hate speech used was stereotype, and finally the media professionals generally did not try to combat hate speech.